Skippyjon Jones - Schachner, Judith Byron
Holy frijoles! Doodle and draw along with Skippyjon Jones, his mother, his sisters, and of course, los Chimichangos in this fun-filled book. Certain to spark creativity and imaginations, readers will love finishing off the doodles, creating their own drawings, and decorating them with stickers